Mechanical Design of Self-Reconfiguring 4D-Printed OrigamiSats: A New Concept for Solar Sailing - Russo, Aloisia; Robb, Bonar; Soldini, Stefania; Paoletti, Paolo; Bailet, Gilles; McInnes, Colin R.; Reveles, Juan; Sugihara, Ahmed K.; Bonardi, Stephane; Mori, Osamu (Frontiers in Space Technologies, 2022)
In this article, a self-reconfiguring OrigamiSat concept is presented. The reconfiguration of the proposed OrigamiSat is triggered by combining the effect of 4D material (i.e. origami’s edges) and changes in the local surface optical properties (i.e. origami’s facets) to harness the solar radiation pressure acceleration. The proposed OrigamiSat uses the principle of solar sailing to enhance the effect of the Sun radiation to generate momentum on the Aluminised Kapton (Al-Kapton) origami surface by transitioning from mirror-like to diffusely reflecting optical properties of each individual facet. Numerical simulations have demonstrated that local changes in the optical properties can trigger reconfiguration. A minimum of 1-meter edge size facet is required for a thick-origami Al-Kapton origami to generate enough forces from the Sun radiation. The thick-origami pattern is 3D-printed directly on a thin Al-Kapton film (the solar sail substrate which is highly reflective). An elastic filament (thermoplastic polyurethane TPU) showed best performance when printing directly on the Al-Kapton and the Acrylonitrile Butadiene Styrene with carbon fiber reinforcement (ABS/cc) is added to augment the origami mechanical properties. The 4D material (shape memory polymer) is integrated only at specific edges to achieve self-deployment by applying heat. Two different folding mechanisms were studied: (1) the cartilage-like , where the hinge is made combining the TPU and the 4D material which make the mounts or valleys fully stretchable, and (2) the mechanical hinge, where simple hinges are made solely of ABS/cc. Numerical simulations have demonstrated that the cartilage-like hinge is the most suitable design for light-weight reconfigurable OrigamiSat when using the solar radiation pressure acceleration. We have used build-in electric board to heat up the 4D material and trigger the folding. We envisage embedding the heat wire within the 4D hinge in the future.